Need help from an expert?
The world’s top online tutoring provider trusted by students, parents, and schools globally.
To integrate tan^4(x), use the identity tan^2(x) = sec^2(x) - 1 and substitution.
First, rewrite tan^4(x) as (tan^2(x))^2. Then, use the identity tan^2(x) = sec^2(x) - 1 to get:
tan^4(x) = (sec^2(x) - 1)^2
Expand the square to get:
tan^4(x) = sec^4(x) - 2sec^2(x) + 1
Now, substitute u = sec(x) and du/dx = sec(x)tan(x) dx. This gives:
∫tan^4(x) dx = ∫(sec^4(x) - 2sec^2(x) + 1) dx
= ∫(u^4 - 2u^2 + 1) du/(u tan(x))
Simplify the integrand by dividing through by u^3 tan(x):
∫tan^4(x) dx = ∫(u - 2/u + 1/u^3) du
Integrate each term separately:
∫tan^4(x) dx = (1/2)u^2 - 2ln|u| - (1/2u^2) + C
Substitute back in for u:
∫tan^4(x) dx = (1/2)sec^2(x)^2 - 2ln|sec(x)| - (1/2)sec^(-2)(x) + C
Simplify the answer by using the identity sec^2(x) = 1 + tan^2(x):
∫tan^4(x) dx = (1/2)(tan^2(x) + 1)^2 - 2ln|sec(x)| - (1/2)(1 + tan^2(x))^(-1) + C
Study and Practice for Free
Trusted by 100,000+ Students Worldwide
Achieve Top Grades in your Exams with our Free Resources.
Practice Questions, Study Notes, and Past Exam Papers for all Subjects!
The world’s top online tutoring provider trusted by students, parents, and schools globally.